Dataset: Masculinities in conservation science, policy and practice - A qualitative systematic review - West, Simon Patrick; Lilford, Oliver; Masterson, Vanessa; Laszlo Ambjörnsson, Emmeline; Austin, Beau; Büscher, Bram; Campbell, Laura-Bethia; Graham, Marnie; Lahiri-Dutt, Kuntala; Schultz, Lisen; Spierenburg, Marja; Wong, Grace; et al. (Stockholm University, 2026)
This project developed a qualitative systematic review of the literature on masculinities in biodiversity conservation science, policy and practice. Data collection consisted of conducted systematic literature searches and screening of the existing academic literature on masculinities in conservation in the databases Scopus and Google Scholar. Data analysis consisted of qualitative content analysis applied to the selected academic literature. The dataset stored here consists of the Excel spreadsheet containing the coded literature included in the review, as well as supporting information including (a) the search and screening documentation, (b) the qualitative coding framework, (c) the full list of articles included in the review, and (d) the completed PRISMA checklist for systematic reviews.
Keywords: Earth and Environmental Sciences; Social Sciences; conservation biology; conservation practice; conservation social science; gender; gender equality; gender identity; intersectional; qualitative systematic review; masculinity; performative; Social Sciences; Samhällsvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap